Characterization of ompA Genotypes by Sequence Analysis of DNA from All Detected Cases of Chlamydia trachomatis Infections during 1 Year of Contact Tracing in a Swedish County - Lysén, Maria (American Society for Microbiology, 2004)
In this study we aimed to characterize the ompA gene by sequencing DNA from all detected cases of Chlamydia trachomatis infection in a Swedish county during 2001, in order to improve the efficiency of contact tracing. Approximately 990 bp of the ompA gene was amplified, and sequence analysis was achieved in 678 (94%) of 725 C. trachomatis-positive cases in this unselected population. The most prevalent genotype was serotype E (39%), followed by F (21%), G (11%), D (9%), K (9%), J (7%), H (2%), B (1%), and Ia (1%). Serotype E was found in five genotype variants, with the reference sequence comprising 96% of all E cases. Serotype D was the most variable, and of seven sequence variants, three were identified as recombinants with serotype E. Altogether 29 genetic variants were detected, and mutations and recombination events are discussed. Clinical manifestations were not associated with genotypes. Sequence variation was linked to sexual networks identified by contact tracing and improved epidemiological knowledge but was of limited benefit.